Insulin resistance and outcome in bipolar disorder - Calkin, Cynthia V; Ruzickova, Martina; Uher, Rudolf; Hajek, Tomas; Slaney, Claire M; Garnham, Julie S; O'Donovan, M Claire; Alda, Martin (The British journal of psychiatry, 2015)
BACKGROUND: Little is known about the impact of insulin resistance on bipolar disorder. AIMS: To examine the relationships between insulin resistance, type 2 diabetes and clinical course and treatment outcomes in bipolar disorder. METHOD: We measured fasting glucose and insulin in 121 adults with bipolar disorder. We diagnosed type 2 diabetes and determined insulin resistance. The National Institute of Mental Health Life Chart was used to record the course of bipolar disorder and the Alda scale to establish response to prophylactic lithium treatment. RESULTS: Patients with bipolar disorder and type 2 diabetes or insulin resistance had three times higher odds of a chronic course of bipolar disorder compared with euglycaemic patients (50% and 48.7% respectively v. 27.3%, odds ratio (OR) = 3.07, P = 0.007), three times higher odds of rapid cycling (38.5% and 39.5% respectively v. 18.2%, OR = 3.13, P = 0.012) and were more likely to be refractory to lithium treatment (36.8% and 36.7% respectively v. 3.2%, OR = 8.40, P<0.0001). All associations remained significant after controlling for antipsychotic exposure and body mass index in sensitivity analyses. CONCLUSIONS: Comorbid insulin resistance may be an important factor in resistance to treatment in bipolar disorder.
Keywords: senioři; Cross-Sectional Studies; Disease Progression; senioři nad 80 let; krevní glukóza; Male; progrese nemoci; mladiství; bipolární porucha; výsledek terapie; inzulin; Middle Aged; mužské pohlaví; Diabetes Mellitus, Type 2; Insulin; studie případů a kontrol; Lithium; průřezové studie; Adult; mladý dospělý; diabetes mellitus 2. typu; Antimanic Agents; Bipolar Disorder; Aged, 80 and over; Blood Glucose; Young Adult; ženské pohlaví; Humans; lithium; antimanika; lidé středního věku; dospělí; inzulinová rezistence; Female; Aged; Insulin Resistance; Adolescent; Treatment Outcome; lidé; Case-Control Studies